Enhanced immunity against SARS-CoV-2 in returning Chinese individuals - Runyu Yuan; Huimin Chen; Lina Yi; Xinxin Li; Ximing Hu; Xing Li; Huan Zhang; Pingping Zhou; Chumin Liang; Huifang Lin; Lilian Zeng; Xue Zhuang; et al. (Human Vaccines & Immunotherapeutics)
Global COVID-19 vaccination programs effectively contained the fast spread of SARS-CoV-2. Characterizing the immunity status of returned populations will favor understanding the achievement of herd immunity and long-term management of COVID-19 in China. Individuals were recruited from 7 quarantine stations in Guangzhou, China. Blood and throat swab specimens were collected from participants, and their immunity status was determined through competitive ELISA, microneutralization assay and enzyme-linked FluoroSpot assay. A total of 272 subjects were involved in the questionnaire survey, of whom 235 (86.4%) were returning Chinese individuals and 37 (13.6%) were foreigners. Blood and throat swab specimens were collected from 108 returning Chinese individuals. Neutralizing antibodies against SARS-CoV-2 were detected in ~90% of returning Chinese individuals, either in the primary or the homologous and heterologous booster vaccination group. The serum NAb titers were significantly decreased against SARS-CoV-2 Omicron BA.5, BF.7, BQ.1 and XBB.1 compared with the prototype virus. However, memory T-cell responses, including specific IFN-γ and IL-2 responses, were not different in either group. Smoking, alcohol consumption, SARS-CoV-2 infection, COVID-19 vaccination, and the time interval between last vaccination and sampling were independent influencing factors for NAb titers against prototype SARS-CoV-2 and variants of concern. The vaccine dose was the unique common influencing factor for Omicron subvariants. Enhanced immunity against SARS-CoV-2 was established in returning Chinese individuals who were exposed to reinfection and vaccination. Domestic residents will benefit from booster homologous or heterologous COVID-19 vaccination after reopening of China, which is also useful against breakthrough infection.